CUDC‐907, a novel dual PI3K and HDAC inhibitor, in prostate cancer: Antitumour activity and molecular mechanism of action. Issue 13 (27th May 2020) - Hu, Cheng; Xia, Hongyan; Bai, Shanshan; Zhao, Jianlei; Edwards, Holly; Li, Xinyu; Yang, Yanrong; Lyu, Jing; Wang, Guan; Zhan, Yang; Dong, Yan; Ge, Yubin
Abstract: Targeting the androgen receptor (AR) signalling pathway remains the main therapeutic option for advanced prostate cancer. However, resistance to AR‐targeting inhibitors represents a great challenge, highlighting the need for new therapies. Activation of the PI3K/AKT pathway and increased expression of histone deacetylases (HDACs) are common aberrations in prostate cancer, suggesting that inhibition of such targets may be a viable therapeutic strategy for this patient population. Previous reports demonstrated that combination of PI3K inhibitors (PI3KIs) with histone deacetylase inhibitors (HDACIs) resulted in synergistic antitumour activities against preclinical models of prostate cancer. In this study, we demonstrate that the novel dual PI3K and HDAC inhibitor CUDC‐907 has promising antitumour activity against prostate cancer cell lines in vitro and castration‐resistant LuCaP 35CR patient‐derived xenograft (PDX) mouse model in vivo. CUDC‐907‐induced apoptosis was partially dependent on Mcl‐1, Bcl‐xL, Bim and c‐Myc. Further, down‐regulation of Wee1, CHK1, RRM1 and RRM2 contributed to CUDC‐907‐induced DNA damage and apoptosis. In the LuCaP 35CR PDX model, treatment with CUDC‐907 resulted in significant inhibition of tumour growth. These findings support the clinical development of CUDC‐907 for the treatment of prostate cancer.